Perception and Use of Herbal Medicine by Medical Doctors - Mulyadi Djojosaputro; Abraham Simatupang; Agus W. Nugroho (Majalah Kedokteran UKI, 2012)
AbstractSince 1995, the Government has encouraged people to establish Centre of Development and Implementation of Traditional Medicine or Sentra Pengembangan dan Penerapan Pengobatan Tradisional (SP3T) through the Ministry of Health’s decree No. 0584/Menkes/SK/VI/1995. At the moment several centers have been realized and provided herbal medicine (HM) in their service. The aim of the survey was to get the picture of the perception and the usage of HM by medical doctors. Questionnaires were distributed by online system to 267 doctors. The results showed that 53% respondents were 41-55 years old, whereas 47% were 40 or younger, more than half (59%) were female. With regards to their medical specializations 29% were GPs, 18%, internists, 6% neurologists and obstetricians, and 41% other specializations. Sixty five percent respondents did not prescribe HM but 35% prescribed occasionally. Those who are not practicing or prescribing HM to their patients stated that they never learnt it (41%), were doubtful to its efficacy (41%), knew nothing about HM (29%), and were concern about the quality (18%). Although HM is relatively cheaper than modern medicine (59%), but 82% respondents stated that information on HM is lacking. They proposed that awareness about HM should be increased through seminars (88%), courses/workshops (53%), journal publication (63%), brochures and leaflets (24%), and medical representative (18%). The use of HM by respondents is mainly for non-specific diarrhea (63%), hypertension and rheumatoid arthritis (38%), hypercholesterolemia (25%) and diabetes mellitus (13%). Respondents agreed that HM should be taught in medical schools (94%) for at least one semester (60%) or two semesters (40%).Keywords: phytopharmaca, medical education, perception, herbal medicine AbstrakSesuai dengan Keputusan Menteri Kesehatan No. 0584/Menkes/SK/VI/1995, sejak 1995 Pemerintah telah menganjurkan masyarakat untuk membentuk Sentra Pengembangan dan Penerapan Pengobatan Tradisional (SP3T). Saat ini sudah ada beberapa pusat pelayanan pengobatan herba. Tujuan survei ini untuk mendapatkan gambaran tentang persepsi dan penggunaan obat herba (OH) oleh para dokter. Kuesioner disebarkan secara daring kepada 267 alumni dan non-alumni Fakultas Kedokteran UKI. Hasilnya memperlihatkan 53% responden berusia 41-55 tahun, 47% berusia sampai 40 tahun, serta 59% terdiri atas perempuan. Dari segi spesialisasi didapatkan 29% dokter umum, 18% spesialis penyakit dalam, 6% spesialis penyakit syaraf dan ahli kandungan sedangkan 41% memiliki spesialisasi lain. Enam puluh lima persen responden tidak meresepkan OH dan hanya 35% responden yang meresepkan secara tidak rutin. Hal itu karena mereka tidak pernah belajar OH (41%), tidak yakin akan efikasinya (41%), tidak tahu sama sekali tentang OH (29%) dan tidak yakin akan mutunya (18%). Meskipun OH relatif lebih murah daripada obat konvensional (59%) tapi 82% responden menyatakan informasi tentang OH sangat kurang. Mereka mengusulkan agar informasi OH ditingkatkan melalui seminar (88%), kursus/lokakarya (53%), publikasi lewat jurnal (63%), brosur dan liflet (24%) dan medical representative (18%). Penggunaan OH oleh responden terutama untuk diare non-spesifik (63%), hipertensi dan artritis reumatoid (38%), hiperkolesterolemia (25%) dan diabetes mellitus (13%). Responden setuju agar OH diajarkan di fakultas kedokteran (94%) sekurang-kurangnya satu semester (60%) atau dua semester (40%).Kata kunci: fitofarmaka, pendidikan kedokteran, persepsi, obat herba